1994
DOI: 10.1111/j.1365-2826.1994.tb00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone‐Releasing Hormone Receptor Messenger Ribonucleic Acid Expression in the Rat Pituitary during Lactation and the Estrous Cycle

Abstract: To study mechanisms underlying the modulation of luteinizing hormone-releasing hormone receptor (LHRH-R) during lactation and the estrous cycle, we used a reverse transcriptase-polymerase chain reaction (RT-PCR) procedure to generate a probe for rat LHRH-R messenger RNA (mRNA). Using primers based on the mouse sequence, we amplified an approximately 300 bp fragment from rat pituitary complementary DNA. This PCR product was shown to be part of LHRH-R cDNA by direct sequencing and by comparing to the rat LHRH-R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 25 publications
2
10
1
Order By: Relevance
“…However, in the previous study (28), the control rats were killed in estrus as compared with controls in diestrus II in this experiment. There is no discrepancy between our present and previous findings because it has been reported that in normal rats in diestrus II, the LHRH-R mRNA levels are 2-3 times higher than in estrus (39,40). The elevation of LHRH-R mRNA in the normal female rats after the daily Decapeptyl treatment found in this study was accompanied by a 2.2-fold rise of LHRH-R protein levels.…”
Section: Discussioncontrasting
confidence: 91%
“…However, in the previous study (28), the control rats were killed in estrus as compared with controls in diestrus II in this experiment. There is no discrepancy between our present and previous findings because it has been reported that in normal rats in diestrus II, the LHRH-R mRNA levels are 2-3 times higher than in estrus (39,40). The elevation of LHRH-R mRNA in the normal female rats after the daily Decapeptyl treatment found in this study was accompanied by a 2.2-fold rise of LHRH-R protein levels.…”
Section: Discussioncontrasting
confidence: 91%
“…Levels of LHb subunit mRNA were determined by Northern blotting with the probe for LHb-subunit (5'-GCCGGCACAGATGCTGGTGGTGAA-3') which was end-labeled with [r-32P]ATP using T4 polynucleotide kinase as described previously [2]. Levels of GnRH-R mRNA were determined by Northern blotting with 32 Plabeled GnRH-R single-stranded DNA probes as described previously [4]. The sequences of primers are as follows: N-primer: 5'-GCCAAAATCATCTTTGCTCTCACG-3' C-primer:…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…The concentrations of LH, follicle-stimulating hormone (FSH) and LH-fJ in sera and anterior pituitary extracts were measured with a double-antibody radioimmunoassay kit provided by NIDDK (Bethesda, MA, USA), and were expressed in terms of the NIDDK reference standards rLH-RP-2, rFSH-RP-1, and LH beta AFP-A805. Amount of GnRH-R mRNA and its binding capacity Figure 1A shows [14,15], where a decline in GnRH-R mRNA was found to be significant after ovulation; but these studies did not also investigate ligand binding by GnRH-R. After ovariectomy, GnRH-R binding had increased by 30% at 2 wk and by 70% at 4 wk. These changes paralleled receptor mRNA concentrations, which tendency is compatible with previous reports [16,17] .…”
Section: Hormone Assaymentioning
confidence: 99%